PHONETICS AND PHONOLOGY IN LETRAS-INGLÊS: SOME PERCEPTIONS OF BRAZILIAN STUDENTS IN PARAÍBA - Penha, Luís Bruno; de Lima, Luana Anastácia Santos; Silva Jr., Leônidas (ARACÊ, 2025)
Phonetics and Phonology study human speech, focusing on individual units (phonemes), syllables, and sentences. This knowledge is essential for teachers when teaching pronunciation. This research addresses the focus on Phonetics of English as a Foreign Language (Fonética da Língua Inglesa) in Letras-inglês at the State University of Paraíba (UEPB), Brazil, where it is realized that a low percentage of final works were produced in Phonetics and Phonology studies between 2019 and 2023. This work aims to identify students’ perceptions when studying Phonetics and Phonology, as well as to assess their importance for English majors, particularly as proficient L2 speakers and future educators. To achieve our objectives, a six-question questionnaire was administered to 22 students from Letras-inglês (in the seventh and eighth semesters) to gather their perceptions of Phonetics of English as a Foreign Language courses. This bibliographic research, classified as both qualitative and descriptive, draws on the contributions of Cagliari (1978), Kelly (2000), Alves (2012), Knight (2012), Katz (2013), Souza (2015) Silva Jr. (2018), Rone et al. (2023) among others. Several factors may contribute to the lack of motivation among students regarding Phonetics and Phonology studies, such as the terminology used and the perceived differences between L1 and L2 sounds. In addition, it is confirmed by the students that these courses are significant for students aiming to speak accurately and become English teachers.